Examining Mediating and Moderating Models on The Relationship Among Management Control Systems, Innovations, and Performance - DWI RATMONO; ERTAMBANG NAHARTYO (The Indonesian Journal of Accounting Research, 2013)
The findings of previous research examining the relationship among management control system (MCS), innovation, and performance remain inconsistent (Bisble and Otley 2004; Chenhall et al. 2011, Dunk 2011). Davila et al. (2009) suggest that future research should focus on the empirical investigation of levers of control (LOC) theory to explain these inconsistent findings. In response to this suggestion, this study aims to examine the mediating and moderating model of the relationship among MCS, innovation, and performance. This study extends Bisble and Otley's study (2004) by using more comprehensive definition and measurement of research variables. Data are collected using mail and e-mail survey to controllers of manufacturing firms listed in the Indonesian Stock Exchange (IDX). Partial Least Square (PLS) is used to test the hypotheses due to its ability to test the presence of multiple dependence relationship of latent variables simultaneously (Hair et al. 2010; Kock 2011). The result of this study supports the mediation hypothesis that the MCS affects performance indirectly through innovation. Overall, this study contributes in explaining the inconclusive and contradictory findings of management accounting prior research.